An Evaluation of CEIT Students’ Opinions On Their Internet Addiction In Terms of Several Variables - Gömleksiz, Mehmet Nuri; Kan, Ayşe Ülkü; Pullu, Emine Kübra (Ankara Bilim University, 2017)
The aim of this study is to investigate internet addiction levels of the students of Computer Education and Instructional Technologies CEIT department in terms of several variables.Study group includes first, second, third and fourth graders enrolled at the department of CEIT in Fırat University in 2013-2014 academic year. Quantitative data were collected by using Internet Addiction Scale developed by Young 1998 and adapted into Turkish by Bayraktar 2001 . It is a six-point Likert type scale and includes 20 items. Qualitative data were collected with a semistructured interview form including six questions developed by the researchers. There are totally 234 students, 109 males and 125 females. Study results revealed that students’ internet addictions changed in terms of time spent on internet, internet use aim variables

Bu çalışmanın amacı Bilgisayar ve Öğretim Teknolojileri Eğitimi bölümü öğrencilerinin internet bağımlılık düzeylerini çeşitli değişkenler açısından incelemektir. Araştırmanın çalışma grubunu 2013-2014 eğitimöğretim yılında Fırat Üniversitesi Eğitim Fakültesi’nde öğrenimine devam eden BÖTE Bölümü 1., 2., 3. ve 4. sınıf öğrencileri oluşturmaktadır. Araştırmada nicel veriler Young 1998 tarafından geliştirilen ve Bayraktar 2001 tarafından Türkçeye uyarlanan İnternet Bağımlılık Ölçeği kullanılmıştır. Ölçek altılı Likert tipindedir ve 20 maddeden oluşmaktadır. Nitel veriler ise araştırmacılar tarafından oluşturulan ve 6 sorudan oluşan yarı yapılandırılmış görüşme formu ile toplanmıştır. Araştırmada 109 erkek ve 125 kadın olmak üzere toplam 234 öğrenci yer almaktadır. Öğrencilerin internet bağımlılıklarının internette geçirilen süre ve internet kullanma amacının çeşitlenmesi değişkenine göre değiştiği belirlenmiştir
BÖTE Öğrencilerinin İnternet Bağımlılığı Düzeylerine İlişkin Görüşlerinin Çeşitli Değişkenler Açısından Değerlendirilmesi